The Influence of Scrap Material to Cost Pricing and Inventory Value Ceramics Creative Product at Bureau for Technology of Ceramics Creative Industry-Indonesia - Normal, Nyoman (International Journal of Economics and Financial Issues, 2019)
The aims of the research about scrap material analysis ceramic creative product were : (1) to know the cost price and inventory before calculate scrap material; (2) to determine the value of scrap material; and (3) to know the influence of scrap material to cost of goods manufactured, cost price, and inventory. The research results shew that : (1) the cost price each unit of ceramic creative product at BTCCI before calculate scrap material were IDR 83,558.30 for mythical bird statue (l8.0-w6.0-h20.0), IDR 351,517.29 for cleanse water place (d32.0-h32.0), and IDR 18,918.79 for incense place (ud4.0-md5.0-dd10.0-h8.0); (2) production process of ceramic creative product at BTCCI create scrap material, that is : castle mass BPC-1 for mythical bird statue, body mass BL-1 for cleanse water place, and body mass BSK-1 for incense place; and (3) the scrap material of castle mass BPC-1 was not influence of cost of goods manufactured, cost price, and inventory mythical bird statue, but it increase actual manufacturing overhead cost. Cost of goods manufactured, cost price, and ending inventory mythical bird statue before and after calculate scrap material were IDR 64,275.62, IDR 83,558.30, and IDR 3,856,537.14. Cost of goods manufactured cleanse water place base scrap material of BL-1 decrease IDR 5,957.92 from IDR 270,397.92 to IDR 264,440.00, cost price decrease IDR 7,745.29 from IDR 351,517.29 to IDR 343,772.00, and ending inventory decrease IDR 214,485.00 from 9,734,325.05 to IDR 9,519,840.05. Cost of goods manufactured incense place base scrap material of BSK-1 increase IDR 52.61 from IDR 14,552.92 to IDR 14,605.53, cost price increase IDR 68.40 from IDR 18,918.79 to IDR 18,987.19, and ending inventory increase IDR 3,156.89 from IDR 873,174.99 to IDR 876,331.88. Keywords: Scrap Material, Cost Price, Inventory, Ceramic Creative Product. JEL Classification: G3 DOI: https://doi.org/10.32479/ijefi.7160